Using Technology to Enhance Reading Comprehension in Middle School Students - Gulchеxrаxоn, Tilаvоldiyеvа (Journal of Innovation in Education and Social Research, 2024)
In this article, the opinions of our country and foreign scientists are mentioned about the use of technology to improve the reading comprehension of secondary school students.